2018
DOI: 10.1177/0894439318779336
|View full text |Cite
|
Sign up to set email alerts
|

Exploring User Responses to Entertainment and Political Videos: An Automated Content Analysis of YouTube

Abstract: On YouTube, videos are always presented together with additional user-generated information about those videos. This social information is presented in the form of number of views, (dis)likes, or comments. However, we know little about the characteristics of social information about entertainment videos. To fill this gap, the present study examined the amount and valence of online entertainment videos' social information and compared this to the social information of online political videos. An automated conte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 47 publications
0
12
0
1
Order By: Relevance
“…The Top Comments are sorted by YouTube based on how many users like versus dislike a comment ( Khasawneh et al, 2020 ). The equivalent of the first five pages of comments – the first 375 comments – or all the comments for each vlog were collected for analysis, whatever number was lower ( Möller et al, 2018 ). The comments were copied and pasted into Microsoft Word.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Top Comments are sorted by YouTube based on how many users like versus dislike a comment ( Khasawneh et al, 2020 ). The equivalent of the first five pages of comments – the first 375 comments – or all the comments for each vlog were collected for analysis, whatever number was lower ( Möller et al, 2018 ). The comments were copied and pasted into Microsoft Word.…”
Section: Methodsmentioning
confidence: 99%
“…In psychology, YouTube is a useful research tool ( Chou et al, 2011 ; Khasawneh et al, 2020 ; Konijn et al, 2013 ; Miller, 2015 ; Möller et al, 2018 ). YouTube can be used to share experiences, to seek mental health information and advice, and to share first-hand experiences of mental illness ( Mertan et al, 2021 ; Naslund et al, 2016 ; Woloshyn and Savage, 2020 ; Yoo and Kim, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…He found that “the top 3% most viewed channels account for 28% of all uploads and 85% of all views” (p. 26). Möller, Kühne, Baumgartner, and Peter (2018) performed an analysis of traces left by users (view numbers, [dis]likes, and comments) using API data, comparing entertainment and political videos. Airoldi, Beraldo, and Gandini (2016) “followed” the YouTube recommender algorithm to study networks of music videos.…”
Section: Youtube: Platforms Algorithms and Social Contextsmentioning
confidence: 99%
“…Given that the use of YouTube has been widely adopted for various purposes staring from education to entertainment (Khan, 2017, Möller et al, 2018, users' comments on videos also helps to make sense about the perceptions of the online community. While YouTube has been abundantly used for the purpose of entertainment (Khan, 2017, Cheng et al, 2013, it has also become a tool for learning (Choi and Behm-Morawitz, 2017).…”
Section: Related Literaturementioning
confidence: 99%